Murder at Ochre Court - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery., 2018)
In the summer of 1898, reporter Emma Cross investigates a shocking death among the bright lights of Newport's high society . . . After a disappointing year as a society columnist for the Herald and staying with her more well-heeled Vanderbilt relatives in New York City, Emma has returned to the salty air, glittering ocean vistas, and grand stately mansions of Newport, Rhode Island, more determined than ever to report on hard news. But for now she<U+2019>s covering the social event of the season at Ochre Court, a coming-out ball designed to showcase Cleo Cooper-Smith, who will be literally on display, fittingly as Cleopatra, in an elaborate tableau vivant. Recently installed modern electricity will allow Miss Cooper-Smith to truly shine. But as the deb ascends to her place of honor, the ballroom is plunged into darkness. When the lights come back on, Cleo sits still on her throne, electrocuted to death. Quickly establishing that the wiring was tampered with, Emma now has a murder to investigate. And the array of eligible suspects could fill another ballroom<U+2014>from a shady New York real estate developer to a neglected sister and the mother of a spurned suitor. As Emma begins to discover this crime has unseen connections to a nefarious network, she puts her own life at risk to shine a light on the dark motives behind a merciless murder.